2014
DOI: 10.1038/leu.2014.298
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy of LGL leukemia: prospective multicenter phase II study by the Eastern Cooperative Oncology Group (E5998)

Abstract: Failure to undergo activation-induced cell death due to global dysregulation of apoptosis is the pathogenic hallmark of large granular lymphocyte (LGL) leukemia. Consequently, immunosuppressive agents are rational choices for treatment. This first prospective trial in LGL leukemia was a multicenter, phase 2 clinical trial evaluating methotrexate at 10 mg/m2 orally weekly as initial therapy (Step 1). Patients failing methotrexate were eligible for treatment with cyclophosphamide at 100 mg orally daily (Step 2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 29 publications
9
90
0
Order By: Relevance
“…38 Previous work by our laboratory and collaborators showed IFN-g is significantly upregulated in T-LGLL patient sera compared to normal donor sera, making this a plausible theory. 23 Second, constitutive activation of STAT1 in LGLL has previously been reported by our laboratory, as well as the possibility of STAT1-STAT3 heterodimer species. 5 It is plausible that VDR and STAT1 could interact in LGLL cells, given the high levels of each in most LGLL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Previous work by our laboratory and collaborators showed IFN-g is significantly upregulated in T-LGLL patient sera compared to normal donor sera, making this a plausible theory. 23 Second, constitutive activation of STAT1 in LGLL has previously been reported by our laboratory, as well as the possibility of STAT1-STAT3 heterodimer species. 5 It is plausible that VDR and STAT1 could interact in LGLL cells, given the high levels of each in most LGLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation occurs in the Src homology 2 (SH2) domain, and was found to confer increased transcriptional activity 6 and correlated with a better therapeutic response to methotrexate therapy. 23 Therefore, we sought to correlate STAT3 Y640F mutation with the presence or absence of VDR. To accomplish this, we surveyed 5 WT STAT3 T-LGLL patients and 5 Y640F STAT3 T-LGLL patients (Fig.…”
Section: Vdr and Stats Are Present In Lgll Samplesmentioning
confidence: 99%
“…The Eastern Cooperative Oncology Group prospective clinical trial suggested that a particular Stat3 mutation, Y640F, predicted response to initial therapy with methotrexate (MTX). 47 The first evidence of Stat5b mutations in human disease was discovered in LGL leukemia, but this mutation is not frequent (2%). 19 The N642H mutation in particular was associated with more aggressive disease and an unusual CD3 …”
Section: Molecular Findingsmentioning
confidence: 99%
“…This theory is supported by the observation that STAT3 mutations are correlated with a larger clone size in LGL leukemia patients. 47 Disease manifestations such as cytopenias and autoimmune diseases then result from the production of proinflammatory cytokines mediated by STAT 3 regulation, as well as attack on marrow and joints by the STAT 3-activated LGL. The key molecular signaling components in LGL leukemia are depicted in Figure 6.…”
Section: Pathogenesis Of Lgl Leukemiamentioning
confidence: 99%
See 1 more Smart Citation